Essential oils of the rhizomes of Alpinia conchigera Griff. and Alpinia latilabris Ridl - Wong, K. C; Lee, B. C.; Lam, Nyee Fan; Ibrahim P. (John Wiley & Sons Ltd, 2005)
The essential oils obtained by hydrodistillation of the rhizomes of Alpinia conchigera and Alpinia latilabris were analysed by capillary GC and GC–MS; 50 compounds were identified in A. conchigera rhizome oil, among which 30 have not been detected previously. The major chemical class was terpenoids, with β‐bisabolene (28.9%), 1,8‐cineole (15.3%) and β‐caryophyllene (10.0%) the major components. A. latilabris rhizomes yielded 33 identified constituents, the majority terpenoids, but the oil was clearly dominated by methyl (E)‐cinnamate (89.5%).